From Neo-Weberian to hybrid governance models in public administration: Differences between state and local self-government - Aleksander Aristovnik; Eva Murko; Dejan Ravšelj (Administrative Sciences, 2022)
Public administration and public governance play a crucial role in society today by ensuring that social needs are met. Due to the constantly changing environment, public governance models have transformed many times, creating differences in public governance practices among public administration institutions, with combinations of contradictory structures and principles that coexist. Accordingly, this paper aims to provide an overview of different public governance models, extract quantifiable elements based on models' principles and examine the extent of layering of different governance models at different levels of public administration in the specific case of the Slovenian administration. Thus, the main focus is on identifying the differences in characteristics of public governance practices between state administration and local self-government. The results show state administration institutions are more strongly characterised by the Neo-Weberian model's principles. In contrast, local self-government institutions are more oriented to managerial public governance and Digital-Era Governance practices. Public managers may regard the results as additional resources for democratic and efficient governing. At the same time, they may provide policymakers with in-depth insights to consider while determining the trajectories of future public administration reforms.
Keywords: 350; Comparative Analysis; Good Governance; hybrid models; local self-government; New Public Management; public governance models; Slovenia; state administration; Weberian public administration